Pengaruh Model Pembelajaran PBL Terhadap Peningkatan Komunikasi Ditinjau Dari Sikap Kemandirian Mahasiswa Kebidanan - Made Susi Lissia Andayani (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The study of Undiksha Midwifery Diploma III students aims to find out: (1) the effect of Problem Based Learning (PBL) learning models on improving communication, (2) the influence of high independence attitudes and low attitudes towards improving communication, and (3) the influence of model interactions learning Problem Based Learning (PBL) with an attitude of independence to communication skills. This research is quasi experiment. The population in this study were 79th semester students of Undiksha Midwifery Study Program. Data in the study were collected through recording documents, questionnaires, and observations. Data analysis in the study was carried out by quantitative descriptive method using two-way analysis of variance (ANOVA) techniques. The results of the Undiksha Midwifery Diploma III study showed that: (1) there was an influence between Problem Based Learning (PBL) and conventional models of communication improvement. student, this is indicated by the results of calculations where Fcount (8,540)> Ftable (3.11), (2) there is an influence of high independence attitude and low independence attitude towards student communication which is indicated by the calculation results where F count (85,544)> Ftable (3.11), and (3) there is a significant interaction effect between PBL learning models and student independence towards communication skills as indicated by the calculation results where F count (6.477)> Ftable (3.11).